Role of endoscopic submucosal dissection in treatment of rectal gastroenteropancreatic neuroendocrine neoplasms - Michał Spychalski; Włodzimierz Koptas; Piotr Zelga; Adam Dziki (Gastroenterology Review)
Introduction : A significant rise in incidence of rectal gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) has been observed in the last decade. Most detected gastroenteropancreatic neuroendocrine tumors (GEP-NETs) are well differentiated and less than 2 cm in diameter. Endoscopic submucosal dissection (ESD) is a new method for endoscopic treatment of such tumors, difficult to resect by conventional endoscopic techniques and thus subject to surgical treatment. Aim: To present the results of the endoscopic treatment of GEP NET tumors in the rectum using ESD in single academic center. Material and methods : From June 2013 to April 2014, 4 cases of GEP-NET in the rectum were treated by ESD in our center. Effectiveness of dissection, complications and tumor recurrence after 3 months of treatment were then retrospectively investigated. Results : The group contained 2 patients with primary rectal GEP-NET (1 male, 1 female; age range: 48–60 years) and 2 with scars after incomplete polypectomy of rectal GEP-NET (1 male, 1 female; 61–65 years). Primary rectal GEP-NET diameters were 0.6 cm and 1.5 cm. Scar resection specimen diameters were 0.7 cm and 1 cm. Mean resection time was 28 min. The en bloc resection rate was 100% (2 of 2) and the histologically complete resection was confirmed in both cases. No foci of neuroendocrine neoplasia were reported in dissected scars. No complications were observed. After 3 months, 3 patients underwent follow-up colonoscopy – no local recurrence was reported. Conclusions : Endoscopic submucosal dissection of rectal GEP-NET should be recommended as a treatment of choice when dealing with lesions over 1 cm in diameter without invasion of the muscle layer. Due to technical difficulties, performing this procedure should be reserved for centers with appropriately trained endoscopic staff.